Strategi Pembelajaran Inovatif Materi Aksara Ulu di SMP Muhammadiyah Tanjung Raja - Kaka Picasso Destani; Jessica Amanda Aulia; Syarifuddin, Syarifuddin (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
Learning in schools needs to be updated to make it more engaging and relevant for students. Lessons should be delivered in a fun and creative way. When lessons are taught in an enjoyable manner, students will not only understand the material more easily, but they will also be more motivated to learn. Therefore, the use of innovative teaching strategies is crucial to create a more lively and interactive learning environment. Creative learning is the key to creating an enjoyable learning atmosphere. The Ulu Script learning uses creative learning. The method in this research employs a case study approach, utilizing bottle relay games and videos to enhance students' understanding of the Ulu Script material. Students not only find the lesson easier to understand, but this method also increases their interest. Based on observations from 14 students, ten students, or 71.43%, said that this method made the Ulu Script material very easy to understand. The other four students, or 28.57%, also mentioned that the method was easy to understand. This shows that using a case study method with a creative approach can improve students' comprehension and interest in learning. Therefore, creative and enjoyable learning has the potential to improve the quality of education in schools.